Japan : 2010 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2010)
Japan's economy is gaining strength, but vulnerability to sovereign risk is rising. The new government has a greater willingness to consider needed fiscal reforms. Timely stimulus and strong external demand have supported the economic recovery. Global events have focused on Japan's fiscal problems, and raised the urgency for fiscal adjustment. Easing measures by the Bank of Japan (BoJ) will help recovery and address the risks of deflation. The banking sector has improved, but faces a number of challenges. An ambitious pro-growth agenda would help support fiscal adjustment.